The Impact of E-Commerce on Financial Management and Accounting Strategies In The Digital Age An Applied Study From The Perspective of Faculty Members at Wadi Al-Shati University and Higher Institutes - Taher Abualhasim Jeiballa (Journal of Scientific and Human Dimensions, 2026)
This study aimed to investigate the impact of e-commerce on financial and accounting management strategies in the digital era, focusing on faculty members at Wadi Al-Shatti University and Higher Institutes. Adopting a descriptive-analytical approach, a questionnaire was administered to a sample of academics and experts. The study found that digital transformation necessitates radical changes in financial control and auditing methods, enhancing decision-making efficiency through real-time data accuracy. However, results revealed significant technical and legislative challenges in the local environment hindering full digital integration. The study recommends updating academic curricula and developing information infrastructure to
Keywords: E-commerce; Financial Management; Digital Accounting